2020
DOI: 10.1002/jmd2.12173
|View full text |Cite
|
Sign up to set email alerts
|

Normal reference ranges for urinary δ‐aminolevulinic acid and porphobilinogen levels

Abstract: Acute hepatic porphyria (AHP) is a family of rare, serious, and potentially life‐threatening metabolic disorders caused by mutations in genes encoding enzymes involved in hepatic heme biosynthesis. AHP is characterized by accumulation of neurotoxic heme intermediates, δ‐aminolevulinic acid (ALA), and porphobilinogen (PBG), which are thought to be causal for the disease manifestations. Novel therapeutic treatments such as givosiran, an RNA interference therapeutic that was recently approved for treatment of adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…OLE data for 1.25 and 2.5 mg/kg are pooled. Reference ranges: ALA ULN, 1.47 mmol/mol Cr; PBG ULN, 0.14 mmol/mol Cr 52 . ALA, delta‐aminolevulinic acid; Cr, creatinine; DB, double‐blind; OLE, open‐label extension; PBG, porphobilinogen; ULN, upper limit of normal…”
Section: Resultsmentioning
confidence: 99%
“…OLE data for 1.25 and 2.5 mg/kg are pooled. Reference ranges: ALA ULN, 1.47 mmol/mol Cr; PBG ULN, 0.14 mmol/mol Cr 52 . ALA, delta‐aminolevulinic acid; Cr, creatinine; DB, double‐blind; OLE, open‐label extension; PBG, porphobilinogen; ULN, upper limit of normal…”
Section: Resultsmentioning
confidence: 99%
“… Upper limit of normal = 1.47 mmol/mol Cr for ALA and 0.137 mmol/mol Cr for PBG based on Agarwal et al 25 …”
Section: Resultsmentioning
confidence: 99%
“…Mean ALAS1 mRNA levels at baseline in the enrolled CHE subjects were elevated approximately twofold relative to that in healthy adults. 24 Similarly, mean baseline ALA and PBG levels were elevated by 5-fold and 107-fold above the upper limit of normal, 25 respectively (Table 2). Givosiran treatment resulted in a mean reduction in urine ALAS1 mRNA of 64.3% on day 36 relative to baseline.…”
Section: Givosiran Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 92%
See 1 more Smart Citation
“…The difference is probably due to the presence of contaminant molecules in the urine, which react with Ehrlich's reagent. Recently, LC-MS/MS measurements of a large number of healthy subjects established the upper limit of the normal values (ULN) of ALA and PBG as 1.47 and 0.137 µmol/mmol creatinine, respectively [50], and it was reported that during an acute attack, these values could reach 40 and 55 µmol/mmol creatinine, respectively [48]. Moreover, sample preparation using a solid-phase extraction (SPE) system allows the detection of concentrations as low as 0.05 µM [49].…”
Section: Ala and Pbg Determinationmentioning
confidence: 99%